MANAGEMENT EVALUATIONS OF SCHOOL OPERATIONAL ASSISTANCE FUNDS (BOS) AT SMP NEGERI 2 TILAMUTA - melisa melisa; syamsinah syamsinah; sitti husna; Risna Sanaba (LP2M Universitas Bina Mandiri Gorontalo, 2022)
The objectives study of this research are to find out the management evaluations of School Operational Assistance Funds (BOS) at SMP Negeri 2 Tilamuta, Boalemo regency. This is a descriptive research by using quantitative approach by determining the school headmaster of SMP Negeri 2 Tilamuta, and students’ parents as the primary data sources, whereas descriptive data support as the secondary data sources. In the other hand, this research uses observation, interviews, and document studies as the data collection methods. The obtained data were the processed and analyzed by using data data anaylis, namely (1). Data reduction (2). Presentation of data (3). Conclusion. Therefore, the results of the study concluded that the evaluation of School Operational Assistance Funds’ management at SMP Negeri 2 Tilamuta is well implemented by involving all the relevant parties, such as the school chairman, BOS treasurer, teacher council staff, students’ parents, and school committees. Furthermore, the stages in the organization, implementation, and accountability reports have been carried out maximally, although there were some factors that became obstacles in the evaluation process of the use of BOS, but the school still overcome it.